A microfluidic electrochemical sensing platform for in situ detection of trace cadmium ions. Issue 38 (20th September 2022) - Yuan, Yang; Jia, Hui; Wang, Jie
Abstract : A microfluidic electrochemical detection platform for cadmium ion detection is proposed. The performance of the detection platform, in terms of the microchannel size and electrode modification, was optimized. The proposed platform demonstrated a good detection of cadmium ions. Abstract : Among various detection and analysis platforms, a microfluidic chip-based electrochemical sensing detection platform is a new type of detection platform. In this study, a microfluidic electrochemical detection platform for cadmium ion detection is proposed, and the performance of the detection platform is optimized in terms of both the microchannel size and electrode modifications. The detection mixing processes of the detector with different microchannel sizes, including the concentration distribution in the channel, pressure decay variation and electrolyte current density variation in the detector, were investigated by finite element model calculations. The analysis shows that the size of the microchannel in the detector affects the fluid and thus further affects the chemical reaction. If the size of the electrode does not match the size of the microchannel, insufficient sample volume will lead to inaccurate measurements, reduced sensitivity and increased detection limits. It was found that the sensitivity of the electrochemical sensor was highest when the size of the microchannel in the chip was 400 μm. After optimization, the optimal detection limit for cadmium ions was 0.03 μg L −1 (S/N = 3). The proposed sensing platform is simple in design and stable in structure, and is suitable for field screening and rapid response to heavy metal contamination events.